HEALTH SAFETY ASSESSMENT OF RICE GENETICALLY MODIFIED WITH BOTH GENES OF BT AND EPSPS USING A MOUSE (M US MUSCULUS) MODEL - X. Mo; Z. J. Tan; M. L. Xu; H. M. Yan (Journal of Animal and Plant Sciences, 2015)
Genetically modified (GM) rice has huge potential in rice production, however, its safety as food or feed remains debatable. In this study, the effects of rice modified with both genes of Bt and epsps on mice were determined by feeding tests and in vitro cytotoxicity assays in order to evaluate the safety of GM rice. The results showed that the survival rate of mice fed with GM rice diet for 245 days was 90% for the male and 100% for the female, not lower than that of mice fed with non-GM rice diet or the formula diet. The average body weight gain of the mouse fed with GM rice diet for 30 days was 20.9 g for the male and 11.6 g for the female, not significantly different from that of the mouse fed with non- GM rice diet or the formula diet. The internal organ indices, blood parameters, and allergenic indicators of mice fed with GM rice diet for 245 days were not significantly different from those of mice fed with non-GM rice diet or both non-GMrice diet and the formula diet. The survival rates of mouse lymphocytes exposed to different doses of whole protein fromboth GM and non-GM rice grains for 2-24 hours in vitro were greater than 90%, not significantly different from each other. These results suggest that GM rice, similar to its non-GM rice counterpart, is a safe feed for mice.
Keywords: Genetically modified rice; Mus musculus; Biosafety assessment; Feeding; Cytotoxicity